Police Strategy in Eradicating Narcotics Trafficking Using Drug Detectors in the Rokan Hilir Legal Area - Rahmad Ramadhan; Risdalina Risdalina; Indra Kumalasari M (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research aims to determine the police's strategy in eradicating drug trafficking by using drug detectors. The method used in this research is normative legal research, namely research into problems by looking at the sources of applicable regulations related to police strategies in eradicating drug trafficking. Normative legal research examines law from an internal perspective with the research object being legal norms. The results of the discussion show that the police strategy in eradicating drug trafficking is carried out through electronic and non-electronic methods. The electronic method used is IMS (Ion Mobility Spectrometry) technology which is capable of detecting traces of drugs based on ion mobility, as well as X-ray technology which can detect drugs hidden in items or the body. Apart from electronic methods, the police also use non-electronic methods such as the use of sniffer dogs to detect the presence of drugs through sharp smell and wet chemistry methods which involve chemical reactions to identify the content of narcotic substances. This combination of strategies allows the police to increase effectiveness in detecting and eradicating drug trafficking, thus narrowing the space for narcotics crime perpetrators